Health effects of immediate telework introduction during the COVID-19 era in Japan: A cross-sectional study - Niu, Qian; Nagata, Tomohisa; Fukutani, Naoto; Tezuka, Masato; Shimoura, Kanako; Nagai-Tanima, Momoko; Aoyama, Tomoki (PloS one, 2021)
Telework has been widely discussed in several fields; however, there is a lack of research on the health aspects of teleworking. The current study was conducted to determine the health effects of teleworking during an emergency statement as evidence for future policy development. This was a cross-sectional study in which we administered an online questionnaire to 5,214 general workers (response rate = 36.4%) from June 2020 to August 2020. Based on working methods during the pandemic, workers were categorized into the office group (n = 86) and telework group (n = 1597), and we characterized their demographics, changes in lifestyle, telework status, physical symptoms, and mental health. The results showed that the workers' residence, marital status, management positions, and employee status affected the choice of the work method. During the emergency, teleworkers experienced more changes in their habits than office workers. In terms of exercise habits, 67.0% of the individuals belonging to the office-telework (OT) group exercised less. Approximately half of the teleworkers were satisfied with their telework, and those in the OT group were less satisfied with their telework than those in the telework-telework (TT) group, and they reported an increase in both working hours and meeting hours. Work-family conflict was more pronounced in the TT group than in the two other groups. Only 13.2% of individuals did not experience any stress in the past 30 days, and all three groups showed varying degrees of anxiety and depressive tendencies. In addition, all teleworkers experienced adverse physical symptoms before and after the emergency. Health issues associated with teleworking should be given adequate attention.